2013
DOI: 10.1017/s0021911812001805
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of the State: Coercion and Consent in Chinese Tibet

Abstract: Although China's Tibetans profoundly mistrust the ideologies of the party-state, associating them with illegitimate practices of domination, protest and revolt are rare and effectively suppressed. This might be seen as quasi-colonial domination, the state securing subjection through the performance of paramount power, demonstrated by its suppression of the 2008 protests, or it could be attributed to a form of indirect rule, by which local officials engage with local leaders to generate hegemonic consent. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…In Yancong, common people approach legal mediation not as the provider of legal and moral guidance but as a counter‐public in which alternatives to state laws can be collaboratively discussed and crafted. In showing the progressive and creative ways in which common citizens and local officials collaboratively strive for consensual and fair government of village affairs, this article joins Chinese anthropologists who have recently begun to approach legal mediation ethnographically and to investigate the plurality of legal life in the Chinese countryside (e.g., Pirie ; Zhao ; Zhu ).…”
Section: Resultsmentioning
confidence: 99%
“…In Yancong, common people approach legal mediation not as the provider of legal and moral guidance but as a counter‐public in which alternatives to state laws can be collaboratively discussed and crafted. In showing the progressive and creative ways in which common citizens and local officials collaboratively strive for consensual and fair government of village affairs, this article joins Chinese anthropologists who have recently begun to approach legal mediation ethnographically and to investigate the plurality of legal life in the Chinese countryside (e.g., Pirie ; Zhao ; Zhu ).…”
Section: Resultsmentioning
confidence: 99%
“…The microlevel, integrative, dynamic perspective of a dyadic nexus fighting two‐front battles could be found particularly useful to understand how an official religion interacts with the state, since it is derived from the case of the registered TJC. Recently, more empirical investigations on presumably anti‐political religious groups (e.g., underground Catholics in Chan ; house church believers in Lin ; Tibetan Buddhism in Pirie ) have shown that there exists more cooperative interaction and mutual understanding than has been previously acknowledged. The perspective illustrated in this article may also shed light on analyses of the relationship between unofficial religion and the state, which have often been examined in a macrolevel, confrontational lens that spotlights the irreconcilability between the state and unofficial religion (e.g., Goldstein ; Kindopp ; Marsh ).…”
Section: Resultsmentioning
confidence: 99%
“…The governance structure is virtually duplicated at four levels: National, provincial, district, and commune. While the state might not be truly “an ideological thing” as defined by Philip Abrams (Abrams, ) in other cases, but the state in Vietnam is arguably like the one in China, which is ubiquitously an ideological entity (Pirie, ). In addition, the CPV operates a separate system running in parallel with the government, which in theory has oversight and inspection functions, but in practice plays a final role in decision making.…”
Section: Party State and The Governance System In Vietnammentioning
confidence: 99%
“…This view is predominantly popular among scholars in the Western world. 2 For discussions on this model, see a sampling:Hall (1994) andPirie (2013). 3 See: Vietnam's constitution (amended in 2013) and the Party's statutes 2015.…”
mentioning
confidence: 99%